Synthesis and Characterization of Dispersion Reinforced Sintered System Based on Ultra Fine and Nanocomposite Cu-Al2O3 Powders - Anđić, Zoran; Vujović, Aleksandar; Tasić, Miloš; Korać, Marija; Kamberovic, Željko (IntechOpen, 2011)
None